The Impact of Electronic Marketing Strategies on the Effectiveness of Communication with Customers: Case Study of Higher Education Services Offices in Muscat, Sultanate of Oman - Al-Busaidi, Mayisa Sulaiman Nasser; Matriano, Maria Teresa (Advances in Social Sciences Research Journal, 2021)
Recent advances in technology have led to the emergence of electronic marketing (e-marketing). E-marketing depends on the strategies used by the organizations. Marketing strategy is a marketing plan designed to achieve marketing goals. The purpose of this study is to identify the impact of e-marketing strategies on the effectiveness of customer communication with higher education services offices, and to measure the effectiveness of this impact, identify the challenges facing both customers and offices in the process of implementing the e-marketing process and find the most appropriate solutions to overcome them. The study used both the descriptive and exploratory research design with application of quantitative and qualitative research methods. The quantitative research method was facilitated through the conduct of survey with 159 customers of five higher education service offices located in Muscat, Oman. The findings revealed that most offices used appropriate strategies to communicate with their customers and there were effective responses from higher education service offices. The collected qualitative data revealed that there are no challenges hindering their e-marketing. The suggestion for organization is to change the electronic marketing strategies used to meet the needs and desires of customers over time, and to keep pace with all the changes and trends in marketing; improving procedures for building confidence and a sense of safety on the site, increasing customers’ awareness of the importance of e-marketing and developing intensive awareness programs targeting schools, universities and institutions. It is concluded from this study that organizations should evaluate the impact of e-marketing strategies on the effectiveness of customer communication with them by collecting the necessary information and data on these customers. The focus should be on the most satisfied customers because they are the ones who can make long-term impacts, and influence the future of the organization and its investments.